2008
DOI: 10.1007/s12072-007-9040-3
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient radiofrequency ablation therapy may induce further malignant transformation of hepatocellular carcinoma

Abstract: Our results showed that even a single heat treatment could induce further transformation of an HCC cell line. Our results suggest that an insufficient treatment of HCC by RFA that enables survival of some cells might induce further malignant transformation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 22 publications
1
45
2
Order By: Relevance
“…Some cells can even survive high temperature from 50-55°C. However, cells can seldom survive temperatures above 55°C [9]. Therefore, it seems that most residual tumor and rapid progression should occur when the temperature is below 55°C, which is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…Some cells can even survive high temperature from 50-55°C. However, cells can seldom survive temperatures above 55°C [9]. Therefore, it seems that most residual tumor and rapid progression should occur when the temperature is below 55°C, which is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…In the study of Obara et al, one of HepG2 sublines showed more than 100% increase in proliferation, marked heat tolerance and no obvious difference in invasive capacities compared with parental HepG2 cells [34]. But the mechanism of HepG2 with rapid proliferation was not further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapid progression in RCC has been rarely reported (24), rapid progression following RFA has been reported in hepatocellular carcinoma (HCC) (25,26). Obara et al (27) reported that insufficient RFA may induce further malignant transformation of HCC. Furthermore, Dong et al (28) demonstrated that insufficient RFA promoted epithelial-mesenchymal transition of HCC cells through protein kinase B and extracellular-signal-regulated kinase signaling pathways.…”
Section: Discussionmentioning
confidence: 99%